Effects of ethylene on yield and floral organ development in soybean (Glycine max) - CHENG Yun-qing; YANG Jun; AN Li-jia; CHEN Zhi-wen; LIU Jian-feng (浙江大学学报. 农业与生命科学版)
The effects of ethylene on flower traits, pollen morphology, yield and so on were investigated by spraying leaves at seedling stage with different concentrations of ethylene inhibitor AVG (aminoethoxyvinylglycine) and precursor ACC (1-aminocylopropane-1-carboxylic acid) in soybean cultivar Tiefeng 31, it's found that total number of flower, flower length, petal length, stamina column length, pollen quantity, pollen tube length, straw weight, pod number and yield per plant increased with the AVG concentration increasing, while abortion ratio of pollen decreased. ACC, the precursor of ethylene showed an opposite effect. Both AVG and ACC treatments had no significant effects on pollen germination ratio. Scanning electron microscope (SEM) observation results showed that AVG treatments promoted pollen length, while distorted deformation of some pollens occurred after ACC treatments.